Pengaruh The New Normal Terhadap Manajemen Perubahan Di Indonesia - Bunayyati Hakimah S. Meliala; Nuri Aslami (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The New Normal makes us all have to be able to accept these very significant changes. In fact, this also occurs in all sectors in Indonesia, both economically, politically, and even in education. All regulations are enforced in order to realize the goal of The New Normal itself, which is so that we can all hinder the progress of Covid-19 cases. Because of these conditions, the government has imposed the PPKM system which has even reached Level 3, WFH (Work From Home), GTPP (Task Force for the Acceleration of Handling Covid-19 ), and the implementation of online teaching and learning processes. Good leaders in the government sector and the corporate sector must turn their heads in the face of changes caused by Covid-19 . The impact it causes is also very visible, from the number of companies that lay off their employees, the occurrence of panic buying at the beginning of the emergence of Covid-19 in Indonesia, and the soaring poverty rate because at that time it was difficult for people to earn a living. But to change it all must start from the people concerned. We all have to work well together. Both the community and the government. If only one-sided goals will never be achieved as we want. I know, maybe for some people this obstacle is enough to be a benchmark for their economy. But in order to realize our goal of inhibiting the increase in Covid-19 , we must be enthusiastic to go through all of this. Change management itself begins because of a truce caused by changing times, globalization, more and more consumer desires, and so on. In this study, the author uses a qualitative approach, which is how the data taken are sourced from valid web pages, scientific journals, and books. For the analysis technique, the writer uses interpretation, content, and narrative techniques.